2015
DOI: 10.1891/2168-6653.29.3.241
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Knowledge Validation Inventory–Revised to Assess Current Training Needs of State-Federal Rehabilitation Counselors

Abstract: Purpose:To identify the current training needs of state-federal rehabilitation counselors and determine if the self-perceived training needs differ for participants who are a certified rehabilitation counselor (CRC) to those counselors with out the CRC credential.Method:A mixed-methods internet-based survey design was utilized and included descriptive, qualitative, and ex post facto approaches on a sample of rehabilitation counselors (N= 341) via the Knowledge Validation Inventory-Revised (KVI-R).Results:The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…With the passage of WIOA, the Rehabilitation Act now mandates that VR agencies, and thus the VR professionals who work within them, engage directly with employers to help their consumers obtain employment. Yet some, perhaps many, VR professionals are uncomfortable with business engagement and do not know how to interact effectively with employers (Beveridge et al, 2015; Chan et al, 2003; Fleming et al, 2014; Schultz, 2008).…”
mentioning
confidence: 99%
“…With the passage of WIOA, the Rehabilitation Act now mandates that VR agencies, and thus the VR professionals who work within them, engage directly with employers to help their consumers obtain employment. Yet some, perhaps many, VR professionals are uncomfortable with business engagement and do not know how to interact effectively with employers (Beveridge et al, 2015; Chan et al, 2003; Fleming et al, 2014; Schultz, 2008).…”
mentioning
confidence: 99%
“…Research has documented a lack of counselor preparation and a need for more training in developing employer relationships (Chan et al, 2003; Froehlich & Linkowski, 2002; Lewis & Patterson, 1998). Results of a recent study that evaluated the training needs of rehabilitation counselors indicated that counselors’ perceived level of preparation was well below their perceived level of importance for many knowledge areas related to job development/job placement and vocational consultation/services for employers (Beveridge, Leconte, Shaine, Del Toro, & Penrod, 2015).…”
mentioning
confidence: 99%